1999
DOI: 10.1073/pnas.96.5.2147
|View full text |Cite
|
Sign up to set email alerts
|

p53 regulates a G 2 checkpoint through cyclin B1

Abstract: The p53 tumor suppressor controls multiple cell cycle checkpoints regulating the mammalian response to DNA damage. To identify the mechanism by which p53 regulates G 2 , we have derived a human ovarian cell that undergoes p53-dependent G 2 arrest at 32°C. We have found that p53 prevents G 2 ͞M transition by decreasing intracellular levels of cyclin B1 protein and attenuating the activity of the cyclin B1 promoter. Cyclin B1 is the regulatory subunit of the cdc2 kinase and is a protein required for mitotic init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
279
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(300 citation statements)
references
References 40 publications
17
279
1
3
Order By: Relevance
“…Adp53 infection strongly reduced the proliferation rate of the Ras-transformed cells (Figure 2a), with a reduction of BrdU incorporation ( Figure 2b) and a preferential accumulation in the G2/M phase of the cell cycle (Figure 2c) as reported in other systems, 19 without induction of apoptosis (Figure 2c; o5% of TUNEL-positive cells in both dl70.3 control virus-and Adp53-infected cells). TUNEL and/or viability controls, to ensure the absence of cell death, were performed in each of the following experiments.…”
Section: P53-induced Growth Arrest Of V-ha-rastransformed Cells Is Assupporting
confidence: 71%
“…Adp53 infection strongly reduced the proliferation rate of the Ras-transformed cells (Figure 2a), with a reduction of BrdU incorporation ( Figure 2b) and a preferential accumulation in the G2/M phase of the cell cycle (Figure 2c) as reported in other systems, 19 without induction of apoptosis (Figure 2c; o5% of TUNEL-positive cells in both dl70.3 control virus-and Adp53-infected cells). TUNEL and/or viability controls, to ensure the absence of cell death, were performed in each of the following experiments.…”
Section: P53-induced Growth Arrest Of V-ha-rastransformed Cells Is Assupporting
confidence: 71%
“…And indeed, loss of p53 as well as loss of its downstream target p21 re-established drug synergism in (colon cancer-derived) HCT116 cells 22 (Supplementary Figure S1H), accompanied by increased γH2AX levels and accumulation of mitotically arrested cells (Supplementary Figures S1I and S1J). Similarly, shRNA-mediated depletion of wild-type p53 in the ovarian cancer-derived cell line A2780 led to increased levels of the G2 checkpoint regulator cyclin B1, 23 as well as decreased levels of carboplatin-induced DDB2 (Supplementary Figure S1L), a p53-inducible gene product involved in mediating carboplatin resistance. 24 In conclusion, ganetespib and platinum act in a synergistic manner to induce death in the majority of ovarian carcinoma cells but not in non-transformed and/or p53-proficient cells.…”
Section: Untransformed Cellsmentioning
confidence: 96%
“…For example, p130 was shown to interact with E2F4 and repress the Cdk1 promoter when p53 was overexpressed in the absence of any DNA damage . Overexpression of p53 regulates the extent of the arrest via Cyclin B1 repression (Innocente et al, 1999). However, the arrest in C4-2 cells can occur independently of Cyclin B1 and its associated kinase activities, as our investigations indicated that following irradiation, there are minimal changes in the p53-deficient DN-p53-C4-2 cells while there are dramatically downregulated Cyclin B1 levels in C4-2 cells (S Ray et al, unpublished data).…”
Section: Discussionmentioning
confidence: 67%